Dishware size and snack food intake in a between-subjects laboratory experiment. Issue 4 (21st May 2015) - Robinson, Eric; Sheen, Florence; Harrold, Jo; Boyland, Emma; Halford, Jason CG; Masic, Una
Abstract: Objective: The use of smaller dishware as a way of reducing food consumption has intuitive appeal and is recommended to the general public. Recent experimental studies have failed to find an effect of plate size on food intake, although the methods used across studies have varied. The aim of the present study was to examine the effect that bowl size had on snack food consumption in a 'typical' snacking context (snacking while watching television). Design: Between-subjects. Setting: Laboratory experiment. Subjects: Sixty-one adult participants served themselves and ate popcorn while watching television. Participants were randomly assigned to serve themselves with and eat from either a small or a large bowl. Results: The use of a smaller bowl size did not reduce food consumption. Unexpectedly, participants in the small bowl condition tended to consume more popcorn (34·0 g) than participants in the large bowl condition (24·9 g; 37 % increase, d =0·5), although the statistical significance of this difference depended on whether analyses were adjusted to account for participant characteristics (e.g. gender) associated with food intake ( P =0·02) or not ( P =0·07). Conclusions: Counter to widely held belief, the use of a smaller bowl did not reduce snack food intake. Public health recommendations advising the use of smaller dishware to reduce food consumption are premature, as this strategy may not be effective.